Preparation of some polyamides of diaminodibenzo-18-crown-6 and Studying their liquid crystalline properties: تحضير بعض البولي اميدات لثنائي امينو ثنائي بنزو-18-تاجي-6 ودراسة خواصها البلورية السائلة - Suliman , Nawal Mahgoub; Mohammed, Abuelgasim Abbaker Abed Elrasoul; El Hasssn , El Jali El Obeid (Journal of Faculty of Education, 2021)
Crown ethers are very important compounds in the extraction of alkali, alkaline earth, and transition metal ions that by formation of complexes with these ions .Crown ether polymers may have more ability of extraction compared with their monomers .In addition these polymers may be less poisonous, inexpensive, and can be used as catalysts. This study had been aimed for preparation of four models, and seven polyamides of dibenzo-18-crown-6. First step in this preparation was the nitration of dibenzo-18-crown-6,followed by reduction of the nitro group .Then the polymerization was carried out in an atmosphere of nitrogen gas .The prepared compounds have been characterized using ( IR ) spectra ,and ( CHN ) mass spectra. The cis and trans diaminodibenzo-18-crown-6 have been analyzed using the proton magnetic resonance spectra ( 1HNMR ) .these results have been in agreement with the expected structure of these products. The inherent viscosity of these polymers was measured, and was found to have intermediate molecular weight .The liquid crystalline properties of these polymers was also studied using Differential Scanning Calorimeter ( DSC ), and hot-stage microscope .The polymers of the trans isomer give a semectic, while those of the cis one did not give any liquid crystalline properties.